Ultrahigh oxygen evolution reaction activity in Au doped co-based nanosheets. Issue 10 (22nd February 2022) - Cai, Chao; Han, Shaobo; Zhang, Xiaotao; Yu, Jingxia; Xiang, Xia; Yang, Jack; Qiao, Liang; Zu, Xiaotao; Chen, Yuanzheng; Li, Sean
Abstract : Manipulating Co oxidation by loading Au atoms can substantially enhance the OER activity of those activated Co ions. Abstract : Oxygen evolution reaction (OER) has attracted enormous interest as a key process for water electrolysis over the past years. The advance of this process relies on an effective catalyst. Herein, we employed single-atom Au doped Co-based nanosheets (NSs) to theoretically and experimentally evaluate the OER activity and also the interaction between Co and Au. We reveal that Au–Co(OH)2 NSs achieved a low overpotential of 0.26 V at 10 mA cm −2 . This extraordinary phenomenon presents an overall superior performance greater than state-of-the-art Co-based catalysts in a sequence of α-Co(OH)2 < Co3 O4 < CoOOH < Au–Co(OH)2 . With ab initio calculations and analysis in the specific Au–Co(OH)2 configuration, we reveal that OER on highly active Au–Co(OH)2 originates from lattice oxygen, which is different from the conventional adsorbate evolution scheme. Explicitly, the configuration of Au–Co(OH)2 gives rise to oxygen non-bonding (ONB ) states and oxygen holes, allowing direct O–O bond formation by a couple of oxidized oxygen with oxygen holes, offering a high OER activity. This study provides new insights for elucidating the origins of activity and synthesizing efficient OER electrocatalysts.